2006
DOI: 10.1007/s00410-006-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on silicate melt immiscibility in the system Fe2SiO4–KAlSi3O8–SiO2–CaO–MgO–TiO2–P2O5 and implications for natural magmas

Abstract: The effect of CaO and MgO, with or without TiO 2 and P 2 O 5 , on the two-melt field in the simplified system Fe 2 SiO 4 -KAlSi 3 O 8 -SiO 2 has been experimentally determined at 1,050°-1,240°C, 400 MPa. Despite the suppressing effect of MgO, CaO, and pressure on silicate melt immiscibility, our experiments show that this process is still viable at mid-crustal pressures when small amounts (0.6-2.0 wt%) of P 2 O 5 and TiO 2 are present. Our data stress that the major element partition coefficients between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Although we cannot exclude that some melt inclusions represent an emulsion of unsegregated immiscible melts, we suggest that most of the compositional range that we observe is controlled by a temperature-dependent evolution of element partitioning between immiscible melts. This is confirmed by experimental data showing that CaO partitioning between the Fe-and Si-rich liquids is indeed strongly dependent on temperature, melt composition, and melt structure (Bogaerts and Schmidt, 2006;Charlier and Grove, 2012), which results in a non-linear CaO vs. SiO 2 trend of immiscible pairs (Fig. 5C).…”
Section: Trapping Of Melt Inclusions and Compositional Evolution Durisupporting
confidence: 80%
“…Although we cannot exclude that some melt inclusions represent an emulsion of unsegregated immiscible melts, we suggest that most of the compositional range that we observe is controlled by a temperature-dependent evolution of element partitioning between immiscible melts. This is confirmed by experimental data showing that CaO partitioning between the Fe-and Si-rich liquids is indeed strongly dependent on temperature, melt composition, and melt structure (Bogaerts and Schmidt, 2006;Charlier and Grove, 2012), which results in a non-linear CaO vs. SiO 2 trend of immiscible pairs (Fig. 5C).…”
Section: Trapping Of Melt Inclusions and Compositional Evolution Durisupporting
confidence: 80%
“…6a-b). Two diagrams are used, with and without TiO 2 , because, although TiO 2 is important for the development of immiscibility (Visser and Koster van Groos 1979b;Bogaerts and Schmidt 2006), our experiments do not discriminate its role as they all have similar TiO 2 content at the onset of immiscibility. Alkalis reduce the liquidus temperature, as well as P 2 O 5 and TiO 2 , which also expand the immiscibility field .…”
Section: 4mentioning
confidence: 99%
“…augite (Grove et al 1992), which is at a higher temperature compared to the binodal. Experiments on liquid immiscibility have mainly been performed on simplified systems (e.g., Roedder 1978;Bogaerts and Schmidt 2006). Consequently, even though phase relations in the system K 2 O-FeO-Al 2 O 3 -SiO 2 are well known (Roedder 1978;Visser and Koster van Groos 1979a;Freestone and Powell 1983) and the effects of other elements such as P 2 O 5 , TiO 2 , CaO, and MgO in reducing or expanding the immiscibility field have been experimentally identified (Watson 1976;Visser and Koster van Groos 1979b;Naslund 1983;Bogaerts and Schmidt 2006), direct application of these results to complex natural basaltic systems is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, experiments also showed that other elements such as TiO 2 and alkalis (Na 2 O+K 2 O) either enlarge the two-liquid field or decrease the liquidus temperature, favoring liquid-liquid unmixing (Watson 1976;Visser and Koster van Groos 1979;Bogaerts and Schmidt 2006;Charlier and Grove 2012). Charlier and Grove (2012) have experimentally shown that silicate liquid immiscibility may develop below 1,000-1,020°C in compositionally diverse tholeiitic lavas at one atmosphere under anhydrous conditions.…”
Section: Cr-rich Titanomagnetite and Cr-poor Titanomagnetitementioning
confidence: 99%